MXene-supported Ni–Co bimetallic MOF 2D lamellar membrane for enhanced electrochemical oxygen reactions and Li–O2 battery - Liming Liu; Hongxia Lian; Heming Deng; Weixin Zhang (Scientific Reports)
Abstract Challenges associated with the cathode material of Lithium–oxygen (Li–O2) battery, particularly the sluggish kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction, as well as the accumulation of discharge product Li2O2, have hindered its further advancement. Here, an in-situ synthesis strategy was adopted to load a bimetallic Ni–Co metal–organic framework (Ni/Co-MOF) onto MXene (Ti3C2) layers. Subsequently, a free-standing and flexible Ni/Co-MOF@Ti3C2 hybrid membrane is prepared via a layer-by-layer self-assembly method, specifically designed for efficient ORR and as a cathode for Li–O2 batteries. The Ni/Co-MOF@Ti3C2 hybrid membrane integrates the high conductivity, unique two-dimensional layered structure, and excellent mechanical properties of Ti3C2 with the bimetallic active sites of Ni/Co-MOF, exhibiting remarkable ORR catalytic activity in an O2-saturated 1 M LiTFSI electrolyte. The structural characteristics of the hybrid membrane provide smoother expansion pathways for Li+ and O2, effectively promoting the deposition and decomposition of Li2O2. This not only enhances the electrochemical performance of the Li–O2 battery but also overcomes the inherent limitations of traditional slurry-based cathode preparation methods. Experimental results demonstrate that Li–O2 batteries utilizing the Ni/Co-MOF@Ti3C2 hybrid membrane as the cathode achieve an ultra-high capacity of 36,125 mAh/g at a current density of 1000 mA/g, while exhibiting excellent cycle stability (271 cycles with a limited capacity of 1000 mAh/g at 1000 mA/g) and outstanding rate performance. The hybrid membrane’s capacity and cycle performance can be further optimized by controlling its thickness. These promising results offer novel insights into the innovative design of air cathodes for metal–air batteries, and the proposed method provides a new route for the manufacture of high-performance battery cathodes.